Epidemiological investigation of a temporal increase in atonic postpartum haemorrhage: a population‐based retrospective cohort study. Issue 7 (6th March 2013) - Mehrabadi, A; Hutcheon, JA; Lee, L; Kramer, MS; Liston, RM; Joseph, KS
<x xml:space="preserve">Abstract</x> Objective Increases in atonic postpartum haemorrhage (PPH) have been reported from several countries in recent years. We attempted to determine the potential cause of the increase in atonic and severe atonic PPH. Design Population‐based retrospective cohort study. Setting British Columbia, Canada, 2001–2009. Population All women with live births or stillbirths. Methods Detailed clinical information was obtained for 371 193 women from the British Columbia Perinatal Data Registry. Outcomes of interest were atonic PPH and severe atonic PPH (atonic PPH with blood transfusion ≥1 unit; atonic PPH with blood transfusion ≥3 units or procedures to control bleeding), whereas determinants studied included maternal characteristics (e.g. age, parity, and body mass index) and obstetrics practice factors (e.g. labour induction, augmentation, and caesarean delivery). Year‐specific unadjusted and adjusted odds ratios for the outcomes were compared using logistic regression. Main outcome measures Atonic PPH and severe atonic PPH. Results Atonic PPH increased from 4.8% in 2001 to 6.3% in 2009, atonic PPH with blood transfusion ≥1 unit increased from 16.6 in 2001 to 25.5 per 10 000 deliveries in 2009, and atonic PPH with blood transfusion ≥3 units or procedures to control bleeding increased from 11.9 to 17.6 per 10 000 deliveries. The crude 34% (95% CI 26–42%) increase in atonic PPH between 2001 and 2009 remained unchanged (42% increase, 95% CI 34–51%) after adjustment for determinants of PPH. Similarly, adjustment did not explain the increase in severe atonic PPH. Conclusions Changes in maternal characteristics and obstetric practice do not explain the recent increase in atonic and severe atonic PPH.